Business applications software for the IBM PC : alternate edition with VP-planner, dBase III/III Plus, and WordPerfect - Ingalsbe, Lon (Toronto, Canada : Merrill Publishing Company, 1988)
This textbook is designed for any course in information systems, business, accounting, or related fields where learning to use applications software as a problem-solving tool is necessary.
Fundamentals of using microcomputers -- Learning lotus -- Learning Wordperfect -- Learning dbase III -- Learning basic A -- Data transfer between applications.
Includes bibliographical references.
Keywords: COMPUTER SOFTWARE